An Assessment of Risk Factors for Herpes Simplex Virus Type 2 Infection in Malawian Women Using 2 Classifications for the HerpeSelect 2 Test. Issue 3 (March 2020) - Chakraborty, Payal; Norris, Alison H.; Huber-Krum, Sarah; Garver, Sarah; Hood, Robert B.; Banda, Venson; Esber, Allahna; Patricia, Carr Reese; Krysiak, Robert; Turner, Abigail Norris
Abstract : Background: The HerpeSelect 2 ELISA IgG test for herpes simplex virus type 2 (HSV-2) infection is widely used, convenient, and inexpensive. However, it has been shown to have lower specificity among populations in Sub-Saharan Africa compared with HSV-2 tests regarded as criterion standards. Methods: In 2016, we collected blood and survey data from 248 women participating in a community-based cohort study in rural Malawi (the Umoyo wa Thanzi project). Using multinomial logistic regression accounting for village-level clustering, we examined unadjusted associations between select demographic and sexual risk factors and HSV-2 serostatus. Because increasing the index value cutpoint for a positive result improves specificity, we coded HSV-2 serostatus in 2 ways: the manufacturer's recommended cutpoints (<0.9, negative; 0.9–1.1, indeterminate; >1.1, positive) and modified cutpoints with improved specificity (<0.9, negative; 0.9–3.5, indeterminate; >3.5, positive). We aimed to investigate whether associations between select risk factors and HSV-2 serostatus varied under the 2 approaches. Results: The prevalence of HSV-2 in this sample was 67% under the manufacturer's cutpoint and 22% under the modified cutpoint. Under both cutpoints, age, household size, number of marriages, and number of pregnancies were associated with HSV-2–positive serostatus. Using modified cutpoints, current bacterial vaginosis (odds ratio [OR], 3.17; 95% confidence interval [CI], 1.35–7.47), partner concurrency (OR, 4.88; 95% CI, 2.54–9.37) and unsure about partner concurrency (OR, 1.91; 95% CI, 1.08–3.38) were associated with HSV-2 seropositivity. Household size, education, and marital status were the only variables significantly associated with indeterminate HSV-2 serostatus using the modified cutpoints. Conclusion: HSV-2-focused interventions informed by identifying individuals likely to have or acquire HSV-2 must be aware that different target populations may emerge depending on which cutpoints are adopted. Abstract : In a study of reproductive-aged women in Malawi, we found that correlates of herpes simplex virus type 2 positivity, diagnosed by the HerpeSelect 2 ELISA IgG test, changed when increasing the threshold for positivity.